Correlation of PON1 polymorphisms with ankylosing spondylitis susceptibility: A case–control study in Chinese Han population. Issue 42 (October 2017) - Xu, Haitao; Qu, Yiming
Abstract : Abstract: Paraoxonase 1 (PON1) modulates the oxidative stress and inflammatory response, thus, it might relate to the risk of ankylosing spondylitis (AS). The aim of present study was to discover the correlation of PON1 polymorphisms (rs662 and rs854560) with PON1 activity and AS risk. Around 128 AS patients and 146 healthy controls were recruited in this case–control study. PON1 polymorphisms were genotyped by direct sequencing. Serum PON1 activity was detected and compared by nonparametric test in different genotypes of PON1 polymorphisms. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to present the relative risk for AS. GG genotype and G allele of rs662 polymorphism were closely correlated with enhanced AS risk ( P  = .034, OR = 2.318, 95%CI = 1.051–5.113; P  = .032, OR = 1.485, 95%CI = 1.033–2.135). PON1 activity was obviously higher in controls than that in AS patients. Significant difference of PON1 activity has been discovered in the different rs662 genotypes ( P  < .01). rs662 GG genotype carriers had the lowest PON1 activity, followed by AG carriers and the AA carriers. Besides, no significant relationship existed between rs854560 genotypes and AS risk. PON1 rs662 polymorphism is significantly correlated with increased AS risk via inhibiting PON1 activity.